Gc-Ms Analysis Of Phytochemical Constituents In Ethanolic Extract Of Punica Granatum Peel And Vitis Vinifera Seeds - K.ASHOK KUMAR,; K.VIJAYALAKSHMI, (International Journal of Pharma and Bio Sciences, 2011)
Plants have been an important source of medicine with high antioxidant activity for thousands of years. Vitis vinifera and Punica granatum are medicinally important plants belonging to the family Vitaceae and Lythraceae respectively. The peels of Punica granatum is a powerful astringent and cure for diarrhea, and also for stomatitis it can be drunk, used as a mouthwash, douche or enema. The Vitis vinifera seeds possess antioxidative, anti-inflammatory, and antimicrobial activities, as well as having cardio protective, hepatoprotective, and neuroprotective effects. In the present study the ethanolic extract of Punica granatum peel, V.vinifera seeds were subjected to GC-MS analysis. Twenty six and sixteen compounds were identified in Punica granatum peel and Vitis vinifera seeds. The major chemical constituents in Punica granatum peel were Glycerin, Hydroxymethylfurfurole, Guanosine and Pyrogallol. Constituents mainly present in Vitis vinifera seed were Linoleic acid, Palmitic acid, gamma-Sitosterol and Glycerin.